Rigidity of Nominal Wages of Non-Production Workers in Industrial Sector - Sulistiyono, Bambang; Susanto, Joko; Rahayu, Astuti (JEJAK: Jurnal Ekonomi dan Kebijakan, 2015)
Excess supply of labor leads to low the levels of nominal wages received by workers. The amount of minimum wage rate exceeds the market wage rate. The determination of minimum wage is a factor manifested in the institutional and regulatory Provincial Minimum Wage or a District Minimum Wage. Unfortunately, it has made nominal wages  difficult to drop below the minimum wage level. High or low level of nominal wages are associated with worker productivity. Further, nominal wages are rigid to go down. If they have increased, they can not be dropped in the future even though the companys performance is declined. Knowing that condition, in designing the remuneration system, an employer should pay attention to the rigidity of nominal wages, so that when  companys performance declines, the company will not be interfered because of the wages burden.  Furthermore, unions and government should consider the rigidity impact of nominal wages that go down. Thus, when macroeconomic conditions deteriorate and companys performance drops, the company will not go bankrupt due to high labor costs. If the company goes bankrupt, the workers will loose their jobs as a result of employment termination, while the government will face the unemployment problem.